The effects of introducing language learning software during the COVID-19 pandemic - Novikov, Philipp (Frontiers in Education, 2022)
The research aimed to investigate the impact of introducing language learning software to university students in the learning environment influenced by COVID -19. It describes the results of an experience with adding daily activities in Elevate, a free language learning application marketed as brain training software for the undergraduate English curriculum. The experiment took place at RUDN University (Moscow, Russia) in 2021 during the COVID-19 pandemic. Participants were engaged in the synchronous distance and face-to-face learning, depending on their location and the current epidemiological situation. Some students alternated between online and offline environments. The research also aimed to analyze the effects of gamification on learning motivation, time management, and language proficiency under different conditions, including limited student-teacher interactions. Research methods included a theoretical analysis of current trends in language training and gamification. Statistical data were collected and processed using the university's digital ecosystem. The research included quantitative data from the experiment and surveys, which consisted of multiple-choice, single-choice, and open-ended questions. The research sample included students from eight countries with CEFR levels of English from B1 to C1. The research results show the effects of language learning software on students' language proficiency, problem-solving skills, and time management. From the results of this research, it can be concluded that schools and universities can use multi-level feedback from participants to maximize the effectiveness of language training and diversify the range of activities included in the curriculum. The results also provide the theoretical basis for e-learning software development and represent a new contribution to the literature.